The analysis of physical performance during official competitions in professional English football: do positions, game locations, and results influence players' game demands? - Beato, M.; Youngs, A.; Costin, A. J. (The Journal of Strength and Conditioning Research, 2024)
This study aimed, first, to verify if physical parameters were different between players' positions during official matches in English professional football, and second, if the game location (H and A) or results (W, L, D) affected players' physical performance. Twenty-five male professional football players of the same team were included in this data analysis (age = 27 ± 9 years) during the 2022-23 season. Players were divided into positions: center backs, wide backs, center midfielders, attacking midfielders, and strikers. The external load parameters were distance covered, high-speed running (HSR), sprinting distance, accelerations, decelerations, and high metabolic load distance (HMLD, meters > 25.5 w·kg-1) that were monitored using global navigation satellite systems Apex (STATSports). Linear mixed models' analysis for positions reported a significant difference in total distance (p = 0.011), HSR (p < 0.001), sprinting distance (p < 0.001), accelerations (p = 0.003), decelerations (p = 0.002), and HMLD (p < 0.001). Centre backs showed the lowest physical performance in the metrics analyzed, whereas players in the other positions frequently displayed a similar physical performance. Regarding locations and results, differences were only found between locations for decelerations (p = 0.041) and between results for HMLD (p = 0.010). In conclusion, physical performance was influenced by players' positions, whereas game location or results seem to not affect physical performance during official competitions. Consequently, practitioners can physically prepare their players independently from the location of the match or of the possible game results, whereas specific positional training is requested to optimally prepare their players.